1997
DOI: 10.1002/(sici)1097-4628(19971107)66:6<1209::aid-app20>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Frontal curing of epoxy resins: Comparison of mechanical and thermal properties to batch‐cured materials

Abstract: ABSTRACT:The epoxy resin diglycidyl ether of bisphenol F (DGEBF) was cured by the aliphatic amine curing agent Epicure 3371 in a stoichiometric ratio both frontally and in a batch-cure schedule. Glass transition temperatures ( T g ) were determined using differential scanning calorimetry (DSC) and dynamic mechanical analysis (DMA). DMA also was used for studying the storage modulus ( E) and tan delta (tan d) of the cured samples. Tensile properties of epoxy samples were tested according to ASTM D638M-93. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 0 publications
1
65
0
Order By: Relevance
“…Although frontal polymerization dates back to the 70 s (46) and has been employed in engineering, chemistry, and astrophysics (47)(48)(49), its use in drug delivery is recent (30). Frontal polymerization is a process of polymerization whereby the reaction is initiated from one end of the sample and then it propagates throughout the sample.…”
Section: Frontal Polymerization For Hydrogelsmentioning
confidence: 99%
“…Although frontal polymerization dates back to the 70 s (46) and has been employed in engineering, chemistry, and astrophysics (47)(48)(49), its use in drug delivery is recent (30). Frontal polymerization is a process of polymerization whereby the reaction is initiated from one end of the sample and then it propagates throughout the sample.…”
Section: Frontal Polymerization For Hydrogelsmentioning
confidence: 99%
“…Since the nineties, a great deal of work has been done mainly by Pojman et al who studied macrokinetics and dynamics [8][9][10][11][12] and new frontally polymerizing systems [13][14][15]; Morbidelli et al suggested the application of FP to the preparation of copolymers [16] and blends [17]; Washington and Steinbock published on the preparation of hydrogels by FP [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Begishev et al studied frontal anionic polymerization of ε-caprolactam [15,16] and epoxy chemistry has been used as well [17][18][19][20]. Mariani et al demonstrated frontal ring-opening metathesis polymerization [21], and Fiori et al produced polyacrylate/poly(dicyclopentadiene) networks frontally [22].…”
Section: Introductionmentioning
confidence: 99%